2015
DOI: 10.1016/j.jacc.2015.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Remodeling and Prognosis Following Kidney Transplantation in Contemporary Patients With Cardiac Dysfunction

Abstract: BACKGROUND Cardiac dysfunction influences candidate selection for kidney transplantation. There is a paucity of data regarding predictors of myocardial recovery following kidney transplantation as well as long-term outcomes. OBJECTIVES The purpose of this study was to identify the extent of reverse remodeling in our kidney transplant population as well as predictors of such changes and assess outcomes in these patients. METHODS We reviewed 232 patients who underwent kidney transplantation at the Cleveland … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
84
4
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(109 citation statements)
references
References 33 publications
10
84
4
6
Order By: Relevance
“…In accordance with previous studies [5,22,24,25], we were able to show that restoration of renal function by KTX ameliorated blood pressure control after KTX and significantly reversed LVH. Of note, all of the investigated 31 kidney transplant recipients in the present study were successfully transplanted (defined as the absence of maintenance dialysis since the date of KTX and a significant improvement of GFR).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In accordance with previous studies [5,22,24,25], we were able to show that restoration of renal function by KTX ameliorated blood pressure control after KTX and significantly reversed LVH. Of note, all of the investigated 31 kidney transplant recipients in the present study were successfully transplanted (defined as the absence of maintenance dialysis since the date of KTX and a significant improvement of GFR).…”
Section: Discussionsupporting
confidence: 92%
“…Improvement of LV systolic function (as determined by LVEF assessment) after KTX was shown in patients with moderately reduced LV systolic function and occurs within a relatively short-term follow-up after KTX [5,28]. In the present study, most patients had preserved or mildly impaired LVEF before KTX, which might explain why we observed only a slight, non-significant increase in LVEF.…”
Section: Discussionsupporting
confidence: 38%
See 1 more Smart Citation
“…Recently, Toblli et al ., in a small randomized trial in patients with HFrEF, ID, and chronic kidney disease, showed that iron sucrose administration translated into a significant 6‐month improvement in LVEF by echocardiography estimation (6.6 ± 3.8%) 5. More recently, findings from a cohort of 232 patients undergoing renal transplantation showed an increase of LVEF, particularly notorious in those with systolic dysfunction pretransplantation 15. Because these changes were strongly and positively related to haemoglobin changes following transplantation, the authors speculated a potential causal link between ID‐anaemia and HF progression in patients with chronic renal failure 15.…”
Section: Discussionmentioning
confidence: 99%
“…10 In addition, assessment of LV mass can be used to monitor response to therapies such as weight reduction 11 or kidney transplantation. 12 Previous work demonstrated the feasibility of using cardiac MRI to derive LV mass in vivo in animals, with excellent correlation to actual measured LV mass ex vivo. 13,14 Additional research optimized cardiac MRI methods for the quantification of LV mass in dogs, leading to high reproducibility and low standard error, 15 with similar results in humans demonstrated by excellent intra-and inter-observer variability.…”
mentioning
confidence: 96%